2008
DOI: 10.1186/1475-2891-7-17
|View full text |Cite
|
Sign up to set email alerts
|

Soy isoflavones, estrogen therapy, and breast cancer risk: analysis and commentary

Abstract: There has been considerable investigation of the potential for soyfoods to reduce risk of cancer, and in particular cancer of the breast. Most interest in this relationship is because soyfoods are essentially a unique dietary source of isoflavones, compounds which bind to estrogen receptors and exhibit weak estrogen-like effects under certain experimental conditions. In recent years the relationship between soyfoods and breast cancer has become controversial because of concernsbased mostly on in vitro and rode… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
104
1
5

Year Published

2009
2009
2022
2022

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 158 publications
(116 citation statements)
references
References 131 publications
1
104
1
5
Order By: Relevance
“…Until now, clinical research has been limited, and there is little clinical evidence to suggest that intake of soy isoflavones increases the risk of breast cancer among healthy women or worsens the prognosis for those who have breast cancer. 17 The results of the Shanghai Breast Cancer Study, conducted between 1996 and 1998, showed that soy intake was unrelated to disease-free breast cancer survival, but the authors of that study did not take endocrine therapy into consideration in their survival analyses. 18 A recent epidemiologic study involving 1954 female survivors of breast cancer also suggested a lower risk of breast cancer recurrence with high intake of daidzein and glycetin among both postmenopausal women and tamoxifen users.…”
Section: Discussionmentioning
confidence: 99%
“…Until now, clinical research has been limited, and there is little clinical evidence to suggest that intake of soy isoflavones increases the risk of breast cancer among healthy women or worsens the prognosis for those who have breast cancer. 17 The results of the Shanghai Breast Cancer Study, conducted between 1996 and 1998, showed that soy intake was unrelated to disease-free breast cancer survival, but the authors of that study did not take endocrine therapy into consideration in their survival analyses. 18 A recent epidemiologic study involving 1954 female survivors of breast cancer also suggested a lower risk of breast cancer recurrence with high intake of daidzein and glycetin among both postmenopausal women and tamoxifen users.…”
Section: Discussionmentioning
confidence: 99%
“…Soybeans are the predominant source of isoflavones. Because of their structural similarity to 17b-estradiol, soy isoflavones may bind directly to the estrogen receptors (ERs) and modulate their functions (Messina and Wood, 2008). Given the association between estrogen and breast cancer risk, it is biologically plausible that dietary soy intake may have an anticarcinogenic effect in the breast.…”
Section: Introductionmentioning
confidence: 99%
“…One of the major differences in diet between these populations is that the Japanese and the Chinese consume a traditional diet high in soy products (35). Epidemiological evidence together with preclinical data from animal and in vitro studies strongly supported a correlation between soy isoflavone consumption and protection towards breast and prostate cancers (45)(46)(47). However, clinical studies assessing soy consumption and risk of breast cancer have yielded inconsistent results.…”
Section: Isoflavones and Prevention Of Cancermentioning
confidence: 99%